PENGEMBANGAN E-LIBRARY SMA NEGERI 10 BULUKUMBA - Rahmat Alghasyiah; Hasrul Bakri; Abdul Wahid Yunus (AGENTS: Journal of Artificial Intelligence and Data Science, 2022)
This studyaims to determine the results of the e-library development of SMA Negeri 10Bulukumba and the results of testing the e-library of SMA Negeri 10 Bulukumbabased on the ISO/IEC 25010 testing standard. This study uses a prototypingdevelopment model, Codeigniter as a framework, built using the PHP programming language. and HTML with MySQL as the database. Data collection techniques using interviews, documentation, and questionnaires. System testing in this studyuses the ISO/IEC 25010 software quality standard focus on aspects of functional suitability, performance efficiency, usability, security, and portability. Based on theresults of testing the functional suitability aspect which was tested by the system expert by filling out a questionnaire containing 83 questions related to the functions designed in the developed e-library, it was concluded from the functionalsuitability aspect that it was acceptable. The results of the performance efficiencyaspect test have met the load time of fewer than 10 seconds. The test results from theusability aspect with 102 respondents and 20 questions obtained good categories. The results of the security aspect test area at the medium-security level. The resultsof the portability test were tested on 6 different devices and browsers, obtainedsuccessfulscoresfrom all devices and browsers.